Analyzing the impact of real and accrual earnings management on the cost of equity: evidence from the Jordanian Amman stock exchange - Ghaleb Al-Qadi, Maher Azzam; Abdul Hamid, Mohamad Ali; Saidin, Saidatunur Fauzi; Abdelrehim, Mahmoud (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the influence of various financial metrics on the cost of equity using a panel data analysis approach, focusing on accrual earnings, real earnings, return on assets, leverage, and firm size. Employing the system Generalized Method of Moments (GMM) technique, we analyze the temporal and cross-sectional effects of these variables. Our findings reveal that both accrual and real earnings significantly affect the cost of equity, with accrual earnings increasing and real earnings decreasing it, highlighting the market's differential valuation of accounting-based versus cash-based profits. Leverage is found to elevate the cost of equity, reflecting the perceived risk of financial distress. Conversely, the relationship between firm size and the cost of equity, while theoretically negative, does not achieve statistical significance, suggesting a complex interaction with equity costs that warrants further investigation. This research contributes to corporate finance literature by elucidating the nuanced impact of financial strategies on equity costs, offering valuable insights for corporate management and investors aiming to optimize financial performance and market valuation.